THE ROLE OF THE DIGITAL ECONOMY IN MANAGING AND IMPROVING THE QUALITY OF LIFE - Mohammed Jassim Abdullah; Hassan Haitham Ismail; Muhammad Hamad Ali Ahmed (Scholars Digest Publishing, 2025)
The transformations that the contemporary world witnessed from the nineties until now are nothing but transformations that imposed themselves on the economy and transformed it from the traditional image to the digital one that resulted in the birth of the digital economy, which led to the multiplicity of names given to our time today, including the digital age, and the era of the gate The information revolution dominating economic and social spaces, the era of the creative electronic mind of new wealth and the post-industrial era, the digital economy has taken center stage in public policy discussions in many countries, mainly developed from them, Almost half of the world's population goes to the Internet and 80% of the citizens of the OECD countries go to fixed and / or mobile broadband.
Keywords: Digital economy, quality of life.